2017
DOI: 10.1080/14767058.2016.1245718
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Great East Japan Earthquake and the Fukushima Daiichi nuclear disaster on the birth weight of newborns in Fukushima Prefecture: Fukushima Health Management Survey

Abstract: We found no evidence that the Great East Japan Earthquake and the Fukushima Daiichi nuclear disaster increased the incidence of SGA in the Fukushima Prefecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…15 The incidence of small-for-gestational age infants was affected by neither area in Fukushima nor trimester of pregnancy at the time of the disaster. 16 Although the delivery rate in Fukushima Prefecture as a whole decreased, the incidence of spontaneous abortion and induced abortion was unchanged compared with that before the accident. 17 The prevalence of congenital anomalies in singleton pregnancies across the 4 years was almost the same as the reported prevalence of 2% to 3% in the general Japanese population ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…15 The incidence of small-for-gestational age infants was affected by neither area in Fukushima nor trimester of pregnancy at the time of the disaster. 16 Although the delivery rate in Fukushima Prefecture as a whole decreased, the incidence of spontaneous abortion and induced abortion was unchanged compared with that before the accident. 17 The prevalence of congenital anomalies in singleton pregnancies across the 4 years was almost the same as the reported prevalence of 2% to 3% in the general Japanese population ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on birth outcomes following the Fukushima disaster have produced mixed results, with some studies finding no significant changes in birth outcomes in areas affected by the nuclear disaster [30,31,32], and others finding increased proportions of low birthweight and preterm births [33]; however, most studies to date have only assessed outcomes within the first year of the disaster. The overall inconsistency within results from Fukushima, and between results from Fukushima and other disasters where increases in low birthweight or preterm births have been predominant indicate that the effects of this disaster may differ from those observed in other settings [9,10,11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited understanding of maternal and perinatal health following this disaster. There has been mixed evidence for immediate post-disaster changes in birth outcomes; some previous studies have found no increased proportions of low birthweight or preterm births in areas affected by the earthquake and tsunami [29], or in areas additionally affected by the nuclear disaster [30,31,32], in the first year post-disaster. However, there have also been findings of a slight increase in low birthweight neonates to women that had been 28–36 weeks pregnant at the time of the earthquake, in earthquake- and tsunami-affected areas [29], and increased proportions of low birthweight and preterm birth to women who conceived within six months post-disaster in areas affected by the Fukushima nuclear disaster [33].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, a few birth cohort studies, which covered all the area within a single prefecture, have been performed in Japan (Fujimori et al 2014;Kyozuka et al 2016;Yasuda et al 2017). The aim of this study is to provide maternal background and adverse obstetric outcome in a single prefecture using largest Japanese cohort study.…”
Section: Introductionmentioning
confidence: 99%